Laboratory evaluation of sodium sulfide injection to facilitate restoration of in situ leached uranium ore zone - W. J. Martin; W. J. Deutsch; R. J. Serne (Society for Mining, Metallurgy & Exploration, 1988)
At the termination of mining, the quality of ground water in the ore-zone aquifer must be returned to a condition predetermined by the permitting agency. To immobilize the redox-sensitive elements (e.g., uranium, arsenic, selenium, molybdenum), it has been suggested that a reducing agent be circulated through the leached ore zone. We have conducted laboratory experiments to test the ability of sodium sulfide as such a reducing agent. Sodium sulfide lowered the redox potential of the effluent such that insoluble minerals containing the redox-sensitive elements should be stable. The uranium concentration of the solution decreased by more than three orders of magnitude. In column experiments, by the time 10 pore volumes of the sulfide solution had flowed through, sulfide minerals were forming. The experimental results indicate that the addition of sodium sulfide should cause chemical reduction of the leached sediments, thereby producing long-term stability of the ground-water/sediment system.